Towards social change : essays on dalit literature - Translating Dalit Literature: Problems and Prospects (Conference) (2010 : Vidyasagar University); Singha, S. P.; Acharya, Indranil; Vidyasagar University. Department of English (New Delhi : Orient BlackSwan, 2014)
Papers presented at the conference on Translating Dalit Literature: Problems and Prospects, held during 23-24 March 2010 organized by Department of English, Vidyasagar University.
Includes bibliographical references.
Keywords: Indic literature -- Translations -- History and criticism -- Congresses; Indic literature -- Dalit authors -- History and criticism -- Congresses; Social change in literature -- Congresses